Answer:
![x=-(3)/(2), x=(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/n14qo60c5u4wio87mtcz1k91xqppx7fkl3.png)
Explanation:
(1) To solve by factoring,
Given equation:
![4 x^(2)=9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ao88xvkcwlw2mawz9v9hjvuo629e7k0ddb.png)
Subtract 9 from both sides of the equation.
![\begin{aligned}&4 x^(2)-9=9-9\\&4 x^(2)-9=0\\&(2 x)^(2)-3^(2)=0\\&(2 x-3)(2 x+3)=0\end{aligned}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dlfj0yg9weonc54b1x9ul9mvtn3qii3q9p.png)
Using zero factor principle,
![2 x-3=0,2 x+3=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/16qq98fpyujqfxj7n7002xigmv0e1ok8pw.png)
The solutions are
.
(2) To solve by complete the square ,
Given
![4 x^(2)=9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ao88xvkcwlw2mawz9v9hjvuo629e7k0ddb.png)
Divide both sides of the equation by 4.
Square root on both sides.
![x=-(3)/(2), x=(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/n14qo60c5u4wio87mtcz1k91xqppx7fkl3.png)
(3) To solve by quadratic formula,
![$4 x^(2)-9=0$](https://img.qammunity.org/2021/formulas/mathematics/middle-school/22cll9o13i54uz60hzrv80mkwzosd0aegd.png)
Here, a = 4, b = 0, c = –9
Quadratic formula,
![$x=\frac{-b \pm \sqrt{b^(2)-4 a c}}{2 a}$](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h0wjsivbrxyic4upfrqf7qjdcnrzgrijem.png)
![x=\frac{-0 \pm \sqrt{0^(2)-4 * 4 *(-9)}}{2 * 4}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/um7d27jqc3u3nqk9atwxwgsohu21o8g5e5.png)
![\begin{aligned}&\Rightarrow x=(\pm √(144))/(8)\\&\Rightarrow x=\pm (3)/(2)\\&\Rightarrow x=(3)/(2), x=-(3)/(2)\end{aligned}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/a1n21gphwoy48rtc9gi0vl3o10aarnxnx5.png)